General practitioners as educators in adolescent health: a training evaluation. Issue 1 (December 2016) - Van de Mortel, Thea; Bird, Jennifer; Chown, Peter; Trigger, Robert; Ahern, Christine
Abstract Background General practitioners play an important role in the primary care of adolescents in both community and clinical settings. Yet studies show that GPs can lack confidence, skills and knowledge in adolescent health. This study evaluates the effectiveness of an innovative training intervention on medical participants' knowledge and confidence as adolescent health educators in a school setting. Methods 15 general practitioners, 12 general practice registrars and 18 medical students participated in an adolescent health education workshop followed by field experience in health education sessions in secondary schools. The mixed method design included a pre and post intervention survey and focus group interviews. Results Mean scores on the Confidence to Teach scale increased significantly (3.34 ± 0.51 to 4.09 ± 0.33) (p < .001) as did confidence to communicate with adolescents (3.64 ± 0.48 to 4.19 ± 0.33) (p < .001). Mean knowledge scores increased significantly (7.00 ± 1.22 to 8.98 ± 1.11) (p < .001). Participants highlighted the value of learning about adolescent health issues and generic teaching skills especially lesson planning and design, practicing experiential teaching strategies and finding the 'sweet spot' when communicating with adolescents. Some participants reported that these skills would transfer to the practice setting. Conclusion An applied training intervention that uses evidence-based, experiential teaching strategies and focuses on developing knowledge and practical teaching skills appropriate for the health education of adolescents can enhance knowledge and confidence to engage in community-based adolescent health education.